PENGARUH LARUTAN PUPUK HAYATI ENDOMIKORIZA ASAL AKAR MERANTI TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KANGKUNG - Matinahoru, Johan (PT. BARRINGTONIA ASIATICA LESTARI, 2024)
Water spinach (Ipomoea sp) is a plant that is widely consumed by people as a vegetable because it is cheap and easy to cultivate. The main problems in growing water spinach are soil fertility and attack by plant pests and diseases. To increase production from kale farming, farmers generally use inorganic fertilizers such as NPK which in reality can cause environmental pollution. For this reason, various efforts to use organic (environmentally friendly) fertilizers such as fungal and bacterial biofertilizers remain the focus of research to date. Mycorrhizal fungi are known to have quite a lot of benefits for plants, especially in providing phosphate and nitrogen nutrients for host plants. In the forestry sector, it is known that the roots of meranti plants (Shorea sp) and the roots of pine plants (Pinus sp) are natural hosts for the growth and development of mycorrhizal fungi. Therefore, the aim of this research is to determine the effect of endomycorrhizal solution fertilizer from meranti roots on the growth and production of water spinach plants. The results of the research show that the endomycorrhizal biofertilizer solution from meranti roots produces growth and production of water spinach plants that are not significantly different from the NPK fertilizer treatment, so from an environmental safety aspect, it is proposed that it is better to use endomycorrhizal biofertilizer because it is environmentally friendly.